The water-energy-food nexus: Bridging the science-policy divide - VAN GEVELT, Terry (Institutional Knowledge at Singapore Management University, 2020)
Although our technical understanding of water–energy–food (WEF) nexus dynamics continues to improve, this knowledge has not yet been translated into effective and implementable policy. My review of the literature suggests that key to bridging the science–policy divide is introducing a political dimension into our understanding of the WEF nexus. By applying insights from the broader area of environmental governance to real-world WEF nexus examples, we see that navigating WEF nexus trade-offs and ensuring the sustainable management of our resources is a ‘wicked’ problem necessarily solved through the political process. By moving beyond an apolitical and positivist conceptualisation of the WEF nexus, we can devise innovative solutions that leverage the contributions of robust science to better manage our WEF resources.